Ekonomi Politik Pembunuhan Massal:Prolog Pembunuhan Massal 1965 di Bali - Pramana, Gede Indra (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2018)
This study focused on the logic behind mass killings to alleged party member and sympathizers of the then legal Indonesian Communist Party in 1965. The events of 1965 has political economy dimensions. In extrapolating the events of 1965, case study on Bali help to explaining the local context of the mass killings. The main question to be answered was, how could there be such large scale killings in 1965?